The axis of risk and uncertainty in hydrologic design - Salas, J. D., author; Burlando, P., author; Heo, J. H., author; Lee, D. J., author; Colorado State University, publisher (Colorado State University. Libraries, 2003)
The uncertainty of the hydrologic risk of flood related hydraulic structures is determined by estimating the variance of the risk of failure based on the methods of moments (MOM), probability weighted moments (PWM), and maximum likelihood (ML) assuming that the underlying model is the Gumbel distribution. The derived variances of the risk based on the three estimation methods are functions of sample size, design life, and nonexceedance probability. Simulation experiments have been performed to analyze the behavior of the risk of failure for various values of the sample size, design life, nonexceedance probability, and coefficient of variation. Two examples are included to illustrate the applicability of the concepts and proposed equations.
Hydrology days 2003
AGU hydrology days 2003
23rd annual AGU hydrology days was held on March 31 - April 2, 2003 at Colorado State University.